Development of chlorine-induced lung injury in the anesthetized, spontaneously breathing pig. (4th May 2021) - Watkins, Rachel; Perrott, Rosi; Bate, Simon; Auton, Philippa; Watts, Sarah; Stoll, Alexander; Rutter, Stephen; Jugg, Bronwen
Abstract: Chlorine is a toxic industrial chemical produced in vast quantities globally, being used in a range of applications such as water purification, sanitation and industrial processes. Its use and transport cannot be restricted; exposure may occur following accidental or deliberate releases. The OPCW recently verified the use of chlorine gas against civilians in both Syria and Iraq. Chlorine inhalation produces damage to the lungs, which may result in the development of an acute lung injury, respiratory failure and death. Treatment remains an intractable problem. Our objective was to develop a clinically relevant pre-clinical model of a moderate to severe lung injury in the pig. This would enable future assessment of therapeutic drugs or interventions to be implemented in the pre-hospital phase after exposure. Due to the irritant nature of chlorine, a number of strategies for exposing terminally anesthetized pigs needed to be investigated. A number of challenges (inconsistent acute changes in respiratory parameters; early deaths), resulted in a moderate to severe lung injury not being achieved. However, most pigs developed a mild lung injury by 12 h. Further investigation is required to optimize the model and enable the assessment of therapeutic candidates. In this paper we describe the exposure strategies used and discuss the challenges encountered in establishing a model of chlorine-induced lung injury. A key aim is to assist researchers navigating the challenges of producing a clinically relevant model of higher dose chlorine exposure where animal welfare is protected by use of terminal anesthesia.